LOGIKA EMPIRISME IBNU TAIMIYYAH DAN RELEVANSINYA TERHADAP STABILITAS EPISTEMOLOGI ISLAM - Muhammad Aviv Nafiudin (UIN Sunan Kalijaga Yogyakarta, 2024)
Islamic civilization in its golden age is a civilization built by the Islamic intellectual tradition with all its developments in intuitive, textual, rational, and empirical areas. However, while Islamic knowledge in the intuitive, textual, and rational areas can be witnessed today, it is not the case with knowledge concerning the empirical area which seems to sink from the paradigm of Islamic thought. Therefore, this research aims to explore the logical structure of Ibn Taymiyyah's empiricism and see its relevance to the stability of Islamic epistemology. To answer these questions, this study uses a qualitative method with the type of library research that refers to two works of Ibn Taymiyyah